THE EFFECTS OF EXTRACTS OF ATRACTYLODES MACROCEPHALA KOIDZ COMBINED WITH TRANSCUTANEOUS ELECTRICAL ACUPOINT STIMULATION IN TREATING THE OVARIECTOMIZED FEMALE RATS - Weng, Qing; Cao, Zhu-Feng; Yu, Yan-Wen; Lv, Xiang-Lin; Qu, Fan; Zhou, Jue (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The present study was to explore the effects of the extracts of Atractylodes macrocephala Koidz (EAMK) combined with transcutaneous electrical acupoint stimulation (TEAS) on the ovariectomized female rats. Materials and Methods: Forty female Sprague-Dawley rats were randomly divided into four groups: sham-operation, model, livial and EAMK+TEAS groups (n=10 in each group). After the individual treatments for 8 weeks ended, the serum levels of estradiol (E2), follicle stimulating hormone (FSH), luteinizing hormone (LH), osteocalcin and interleukin-6 (IL-6) were measured with commercial enzyme-linked immunosorbent assay. Results: We found that in the sham-operation group, the serum E2 and osteocalcin levels were significantly higher, and the serum levels of FSH, LH and IL-6 were markedly lower than those of other groups (P<0.05). No significant differences existed between the livial and EAMK+TEAS groups on the serum E2 and osteocalcin levels (P>0.05), however, the serum FSH and IL-6 levels of EAMK+TEAS group were significantly lower than those of the livial group (P<0.05). Conclusion: EAMK combined with TEAS has promises in treating the ovariectomized female rats.